Socio-Economic and Demographic Pattern of HIV Occurrence Amongst Attendees in a Tertiary Care Hospital in Eastern India. - Firdaus Rushna; Saha Kallol; Pal Jotirmoy; Roy Arnab; Chandra Sadhukhan Provash (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
Objective: Toanalyze the socio-economic pattern amongst HIV patients in eastern and north-eastern India as measured by different parameters such as educational status, wealth, marital status, sexual behaviour. Methods: This study involved 650 HIV seropositive individuals enrolled in a HIV Apex Clinic in a tertiary care hospital in Kolkata, India during 2006 to 2011. Socio-demographic data were obtained while keeping the names of HIV seropositive individual’s names confidential. HIV testing was done according to the guidelines of NACO, India. Diagnoses of different common opportunistic infections were also done. Results: Out of the 650 individuals, 53% reported to have presenting symptoms of low grade fever, 21% had weight loss, general weakness and malaise. 13% reported to have frequent skin rashes, 13% ported to severe seizures and lack of coordination. 41.07 % of them had an income ranging from Rs1000 - 1500 per month. These individuals mainly were daily workers, labourers who work in per day income basis. 44.13% (89 out of 202) of the females were married at a young age, 65 (32.17%) were widowed whose husbands succumbed to HIV. Assessment of the educational qualifications reveals that those individuals affected reveals that 65% of the males received education till standard VIII, 25% received elementary education till standard IV. Conclusion: The study highlights the sectors of the socio-economic class who need more attention to tackle the HIV burden. The analysis of the socio-economic status reveals the low income and lack of education are main contributing factors towards the spread of this disease in this region.
Keywords: Human immunodeficiency virus (HIV)